Chemical Composition and Acaricidal Activity against Tetranychus urticae of Essential Oil from Marsypianthes chamaedrys (Vahl.) Kuntze - Callejon, Daniel R.; Feitosa, Luis G. P.; Silva, Denise B. da; Bizaro, Aline C.; Guaratini, Thais; Lopes, Jose N. C.; Pannuti, Luiz E. R. [UNESP]; Baldin, Edson L. L. [UNESP]; Junior, Milton G.; Cunha, Fernando Q.; Ferreira, Sergio H.; Lopes, Norberto P. (Brazilian Chemical Soc, 2016)
Marsypianthes chamaedrys (Vahl.) Kuntze, known as paracari, erva de cobra, boia-caa or betonia brava, is a common herb in Brazil (North and Northeast regions). The aerial parts (leaves and stem) of this plant were used to essential oil extraction. The essential oil obtained was evaluated against Tetranychus urticae showing no significant acaricidal activity. Analysis by GC-MS was performed and 29 compounds were identified and the main compounds were the sesquiterpenes beta-caryophyllene (12.2%), bicyclogermacrene (17.9%) and germacrene D (34.1%).
Keywords: Marsypianthes chamaedrys; Tetranychus urticae; sesquiterpene; GC-MS